2014
DOI: 10.1039/c4ra06936f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of monocarboxylic acid-modified CeO2 nanoparticles using supercritical water

Abstract: This study reports a simple, rapid synthesis technique for the preparation of monocarboxylic acid-modified CeO2 nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 58 publications
(157 reference statements)
3
40
1
Order By: Relevance
“…The crystallite (particle) size was approximately 7.4 nm [31]. Large CeO 2 crystal (99.9%), as a reference heterogeneous catalyst, denoted as LC (Large crystal), was purchased from Aldrich; the crystallite size is approximately 75 nm determined from the peak width of XRD pattern.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystallite (particle) size was approximately 7.4 nm [31]. Large CeO 2 crystal (99.9%), as a reference heterogeneous catalyst, denoted as LC (Large crystal), was purchased from Aldrich; the crystallite size is approximately 75 nm determined from the peak width of XRD pattern.…”
Section: Methodsmentioning
confidence: 99%
“…In practice, the depolymerization reaction of them depends on the amount of amine reagents, suggesting that the reaction is equimolar and noncatalytic. To construct processes and systems for the industrial production of chemical recycling, mass disposal, mild conditions, short reaction times, simple separation and refinement procedures, high recovery rates (monomer yield), economy, and environmentally friendly conditions [29][30][31]. During these studies, the crystallization of CeO 2 under these conditions was thoroughly investigated, and we succeeded in controlling crystallinity factors such as particle size and morphology.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Assuming that the crystal growth occurred with the dissolution-recrystallization process as suggested by the previous study [11], one has to take account of dissolution of powder into precursors such as Al 3+ , Al(OH) 2+ , Al(OH) 2 + , Al(OH) 3 and Al(OH) 4 − , transportation in solution, diffusion on particle surface, crystallization reaction, and modification reaction. The previous studies also imply the existence of intermediates consisting of particle precursors and modifiers, which can enhance the crystal growth of particles [10,11,13]. These steps have their own temperature dependences, and at certain temperature the specific step(s) should play the rate-determining role.…”
Section: Introductionmentioning
confidence: 99%
“…As one of methods for controlling particle shape, the hydrothermal crystallization using capping agent has also been proposed [9]. It has been reported that the particle shape synthesized under supercritical hydrothermal condition with a carboxylic acid was controlled by the capping effect [10], although the size and aspect ratio of particles did not change drastically because the reaction was terminated immediately after nucleation.…”
Section: Introductionmentioning
confidence: 99%